E0479 Impacts of successful percutaneous coronary intervention for chronic total occlusions on patients with heart dysfunction. (17th November 2010) - Han, Yaling; Yi, Xianhua; Wang, Shouli; Jing, Quanmin
Abstract : Introduction: Successful percutaneous coronary intervention (PCI) for chronic total occlusion (CTO) had proven benefit for long-term survival. However, its impact on heart function of patients with heart dysfunction is uncertain. The purpose of the present study was to analyse the impacts on heart function of patients with heart dysfunction who underwent successful PCI for CTOs. Methods: Between June 1993 and December 2007, the clinical data of 472 consecutive patients with heart dysfunction in our center underwent PCI for CTOs were analysed. The mean age was 59.4±11.5 years. These patients were divided into two groups according to the procedural success (n=421) or failure (n=51), in order to compare the heart function between groups. A follow-up echocardiogram examination was performed 6 months after PCI. Results: 391 (92.9%) patients in CTO success group and 46 (90.2%) patients in CTO failure group accepted the examination of echocardiogram at mean time of 6.2±1.7 months. For patients underwent success CTO revascularisation, left ventricular ejection fraction (LVEF) was increased from 44.5±3.2% to 50.2±5.7% (p<0.05), and left ventricular end-diastolic volume index (LVEDVI) was declined from 84.7±14.3 ml/m 2 to 78.4±13.7 ml/m 2 (p<0.05). But the LVEF and LVEDVI had no significant changes in the CTO failure group (42.5±4.0% vs 43.6±4.1% and 86.8±14.4 ml/m 2 vs 85.9±14.7 ml/m 2, both p>0.05), respectively. In addition, stage of NYHA classification was improved in most people in CTO success group (p<0.05). Conclusions: Successful procedures of CTO leads to the improvement of left ventricular function of patient with heart dysfunction.